Effectiveness and safety of cyclosporine in pediatric plaque psoriasis: A multicentric retrospective analysis. (2nd September 2016) - Di Lernia, V.; Stingeni, L.; Boccaletti, V.; Calzavara Pinton, P. G.; Guarneri, C.; Belloni Fortina, A.; Panzone, M.; Corazza, M.; Neri, I.; Cambiaghi, S.; Lasagni, C.; Ficarelli, E.; et al.
Abstract: Background : Cyclosporine (CysA) is effective for psoriasis in adult patients but little data exist about its efficacy and safety in childhood and adolescence psoriasis. Objectives : To assess the effectiveness and safety of CysA for childhood and adolescence psoriasis. Methods : Retrospective analysis of a group of children and adolescents (age < 17 years) with plaque psoriasis treated with CysA at several Italian dermatology clinics. Results : Our study population consisted of 38 patients. The median age at the start of treatment was 12.3 years. Therapy duration varied from one to 36 months. The median maintenance dosage per day was 3.2 mg/kg (range 2–5 mg/kg). Fifteen patients (39, 4%) achieved a complete clearance or a good improvement of their psoriasis defined by an improvement from baseline of  ≥75% in the psoriasis area and severity index (PASI) at week 16. Eight patients (21.05%) discontinued the treatment due to laboratory anomalies or adverse events. Serious events were not recorded. Conclusions : In this case series, CysA was effective and well-tolerated treatment in a significant quote of children. CysA, when carefully monitored, may represent a therapeutic alternative to the currently used systemic immunosuppressive agents for severe childhood psoriasis.